Price setting and macroeconomic variables: evidence from brazilian CPI - Barros, Rebecca Wellington dos Santos (2009)
This thesis investigates price-setting in a variable macroeconomic environment using a unique data set from the Brazilian CPI index of Fundação Getulio Vargas. The primary data consist of a panel of individual prices for goods and services covering 100% of the CPI for the 1996-2008 period. During this period a number of important events produced substantial macroeconomic variability in Brazil: two emerging market crises, a change of exchange rate and monetary regimes, blackouts and energy rationing, an election crisis, and a regular disinflation. As a consequence, inflation, macroeconomic uncertainty, exchange rates, and output exhibit important variation in the sample. In the first chapter we describe the data-base and present the main price-setting statistics for Brazil. Then, in the second and third chapters, we construct time series of price-setting statistics and temporary sales and relate them to macroeconomic variables using regression analyses. We find that there is a substantial relationship between price setting statistics and the macroeconomic environment for the Brazilian Economy.